Proposal for a web portal managing registration for student accommodation in a dormitory - Podunavac, Ivor (Array, 2019)
A proposal for developing a database model and a web portal for managing registration for student accommodation in a dormitory is given in this paper. The portal has two user profiles and corresponding functionalities; they are intended for users/students and administrators, respectively. In the process of application for student accommodation in a dormitory, every student has to provide data referring to GPA, i.e. academic achievement at school, level of education, university, parents’ status, household members, the number of siblings and their school age, and household monthly income. There are also extra conditions that could ensure direct allocation of accommodation at a dormitory. After the application process deadline has expired, the administrator can either accept or decline applications. At the end of the application process, the final ranking list can be published and made accessible. Advantages of using a web portal for the dormitory accommodation election and application process are e.g. better accessibility and the fact that students are exempt from delivering the necessary application documentation personally. In that way, costs are reduced, efficiency at work is increased and the possibility of making errors when entering and processing data is significantly lower.